Implementasi Gaya Kepemimpinan Situasional Kepala Sekolah SMKS ST.Nahanson Parapat Sipoholon - Hotmarito Hutabarat; Tia Murni Tampubolon; Rapita Banjarnahor; Rico M Sihotang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Leadership style can be defined as a collection of a person's behavior that aims to change and influence the minds of other people so that they are willing to follow the instructions and directions given. This research is a type of qualitative research that uses a descriptive approach. The aim is to explain and describe information obtained from the field as data in research. The location of this research was at SMKS St. Nahanson Parapat Sipoholon, the research subject is the principal at SMKS St. Nahanson Parapat Sipoholon. The data analysis method used refers to the theory of Miles and Huberman, which consists of several steps as follows: 1). Data Collection: Researchers collect data through interviews, observation and documentation. 2). Data Reduction: Researchers carry out selection returning to the data that has been collected at the data analysis stage. 3). Data Presentation: The reduced data is presented by the researcher at this stage. 4). Drawing Conclusions: Before drawing conclusions, the researcher double-checks the data that has been collected. Leadership is the ability and readiness of an individual to influence, encourage, invite, guide, mobilize, and if necessary force others to act in achieving organizational goals. Situational leadership is a leadership approach in which the leader's behavior is adapted to the varying conditions and situations of each subordinate. Indicators that influence situational leadership include: (a) the telling dimension, where the leader gives clear instructions when assigning; (b) selling dimension, which involves two-way communication between leaders and subordinates; (c) participating dimension, which includes assigning tasks and responsibilities to subordinates and supporting leaders in carrying out these tasks; and (d) the delegation dimension, where the leader gives authority to subordinates to act independently. At St. Mary's Vocational School Nahanson Parapat, the situational approach adapts leader behavior to specific conditions and subordinate needs, with four main styles, namely telling, selling, participating, and delegating. Situational leadership has been implemented with examples of implementation by the Principal practicing a telling approach in exam preparation, using selling in discussing new teaching scheduling, and participating in Prakerin planning. However, the delegating style is less applied because the Principal tends to control all aspects of decisions and tasks. In practice, situational leadership at St. Nahanson Parapat faces several obstacles, including the school environment and staff characteristics, which influence the effectiveness of implementing this leadership style. These obstacles require special strategies to overcome them, so that situational leadership can be more effective and adapt to existing situations, so that organizational goals are achieved optimally.